Codeswitching in the Egyptian Arabic Movies: How do social variables trigger codeswitching? - Hassan, Randa (AUC Knowledge Fountain, 2024)
Abstract This is a qualitative study designed to examine the growing linguistic practice of codeswitching in a sociolinguistic context. For this purpose, 7 Egyptian Arabic films were purposefully selected to investigate what social variables and contexts can be associated with codeswitching. Data was sampled in 43 experts from the 7 films. The data was analyzed in terms of the social variables of education, social class, identity, stance, and age, within the theoretical framework of the critical discourse analysis, the accommodation theory, and the social arena theory. Although the study started with these social variables in mind, data analysis revealed two additional variables that may trigger codeswitching: jobs and intense emotions. Moreover, the study concludes that codeswitching is not merely a product of linguistic factors but also because of sociological reasons. In addition, it poses a few questions that highlight more aspects of codeswitching that may interest future research.